Evaluation of a training program for rheumatic heart disease screening integrated into the public health system in Uganda - Paul W. Warren; Scott Wirth; Jafesi Pulle; Doreen Nakaagayi; Charles Oyoo Akia; Evelyn Ayaa; Michaela Pardo; Francis Odong; Ronald Ogwanh; John Omagino; Isaac Otim; Craig Sable; et al. (PLoS ONE, 2026)
Introduction Echocardiography screening for rheumatic heart disease (RHD) has gained support as a public health approach, but scale up of RHD screening services is complex. We sought to evaluate the effectiveness of a novel training program to build non-expert competency for RHD echocardiography screening within the Uganda public health system and to describe the human and material resources required to support it. Methods Guided by a logic model, we evaluated the Accelerating Delivery of Rheumatic Heart Disease Prevention in Northern Uganda (ADUNU) Program, a novel RHD control program, 15 months after its implementation within the Ugandan public health care system. Results Sixty-one healthcare workers (HCW) across 10 public health facilities started in training under the program, of which 58 (95%) advanced past the initial stage of training and earned conditional certification to screen for RHD with ongoing remote and in-person feedback and oversight. Of these, 17 (29%) completed all stages of training and earned full certification to independently screen for RHD with no ongoing oversight. A total of 17,927 community members were screened through ADUNU during the program’s first 15 months. After receiving final certification, 14 HCWs (93%) continued to perform screening echocardiograms (≥20/month) at median follow-up of 8 months [IQR 8–10]. HCW sensitivity and specificity were 61% and 96%, respectively. Conclusion Development and deployment of a large scale RHD screening echocardiography training program within an existing public health system is feasible. Future program iterations are needed to improve HCW screening sensitivity and decrease the reliance on human resources.